Synthesis, Crystal Structure of Tetra-Nuclear Macrocyclic Zn(II) Complex and Its Application as Catalyst for Oxidation of Benzyl Alcohol - Li Hua Wang; Zi Jian Wang; Mei Li Zhao; Xi Shi Tai; Jian Ouyang; Yun Fei Li; Wei Zhang; Wen Lei Jia (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2021)
A new six coordinated tetra-nuclear macrocyclic Zn(II) complex, ZnL4(Phen)2 (1) (HL= 3-bromo-2-hydroxybenzaldehyde-pyridine-2-carbohydrazone, Phen = 1,10-phenanthroline) has been synthesized by the self-assembly of 3-bromo-2-hydroxybenzaldehyde-pyridine-2-carbohydrazone, Zn(CH3COO)2•2H2O, NaOH and 1,10-phenanthroline in water/ethanol (v:v = 1:3) solution. Complex 1 was characterized by elemental analysis, infra red (IR), and single-crystal X-ray diffraction (XRD) analysis. The results show that Zn1 and Zn1b ions are six-coordinated with a distorted octahedral geometric configuration by four O atoms of two different L ligands and two N atoms of two different L ligands, Zn1a and Zn1c ions are also six-coordinated with a distorted octahedral geometric configuration by two N atoms of two different L ligands, two N atoms of Phen ligands and two O atoms of two different L ligands. Complex (1) forms 3D network structure by the - interaction. The selective oxidation reactions of benzyl alcohols catalyzed by complex (1) was investigated. The highest benzyl alcohol conversion and benzaldehyde selectivity were obtained at 100 °C for 4 h under 5 bar of O2. Copyright © 2021 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).